Phylogenetic Studies of the Three RNA Silencing Suppressor Genes of South American CTV Isolates Reveal the Circulation of a Novel Genetic Lineage - María José Benítez-Galeano; Leticia Rubio; Ana Bertalmío; Diego Maeso; Fernando Rivas; Rodney Colina (Viruses, 2015)
Citrus Tristeza Virus (CTV) is the most economically important virus of citrus worldwide. Genetic diversity and population structure of CTV isolates from all citrus growing areas from Uruguay were analyzed by RT-PCR and cloning of the three RNA silencing suppressor genes (p25, p20 and p23). Bayesian phylogenetic analysis revealed the circulation of three known genotypes (VT, T3, T36) in the country, and the presence of a new genetic lineage composed by isolates from around the world, mainly from South America. Nucleotide and amino acid identity values for this new genetic lineage were both higher than 97% for the three analyzed regions. Due to incongruent phylogenetic relationships, recombination analysis was performed using Genetic Algorithms for Recombination Detection (GARD) and SimPlot software. Recombination events between previously described CTV isolates were detected. High intra-sample variation was found, confirming the co-existence of different genotypes into the same plant. This is the first report describing: (1) the genetic diversity of Uruguayan CTV isolates circulating in the country and (2) the circulation of a novel CTV genetic lineage, highly present in the South American region. This information may provide assistance to develop an effective cross-protection program.